Розробка системи рейтингів для закладів вищої освіти України - Zgurovsky, M.; Pankratova, N.; Bobovkin, V.; Linovitskaya, O. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
A system of determination of university ranking in Ukraine was developed based on the creation of the corresponding methods adequate to the structure, peculiarities and conditions of the Ukrainian universities functioning. A complex of organizational and program-technical means was proposed for collection of the necessary data and determination of university rankings. For specialists in the field of higher education management, those seeking for higher education and employers.